MIGRATION ET INTEGRATION SOUS REGIONALE DANS L’ESPACE UEMOA/CEDEAO : APPORT DU LASSO DANS LE DIAGNOSTIC ET L’ACCOMPAGNEMENT DES DYNAMIQUES TRANSFRONTALIERES D’ACCES A L’EDUCATION, LA SANTE ET LA PROTECTION SOCIALE DANS LES REGIONS DU PORO, BAGOUE ET - Euloge, Guehi Zagocky; Issiaka, Kone (European Scientific Journal, ESJ, 2015)
This study addresses the issue of migrations and sub-regional integration in the WAEMU/ECOWAS. It is interested in migrants’ access to public services of education, health, social protection and local dynamics of integration provided by civil society organizations (CSOs) and decentralized territorial authorities. More precisely, it shows the strategies implemented by LASSO and the outcomes resulting from the participatory approach used for the diagnosis and support of cross-border dynamics for the access to education, health, social protection’s public services in the regions of Pôrô, Bagoué and tchologo. From this work, it emerges that the access to utilities of education, health and social protection can constitute an alternative way to build social integration which is not an identity branding. Another result is the vital role that the social scientists can play through a commitment as actors of social change with a closer involvement of local actors in the initiatives for local purposes.